2019 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--32738
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Students’ Self-Reflections, Teamwork Behaviors, and Academic Performance

Abstract: She is interested in exploring the effects of using technology to enhance students' learning. Further, she is interested in understanding the ways and interventions that can be designed to deal with conceptually hard concepts in STEM courses especially programming and software engineering courses. Prior to Purdue University, Saira worked as Assistant Professor in Computer Science Department at Forman Christian College (A Chartered University) at Pakistan for eight years and was recognized for outstanding teach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Thus, they can be used to measure others’ perceptions as well as provide insight into real behaviors (Martel et al, 2017). Indeed, peer team member ratings are positively related to experience level (Nuñez-Thompson et al, Accepted) and objective performance outcomes in real-world teams (Anwar et al, 2019; Ohland et al, 2012). Peer ratings are widely used in academic settings and are projected to increase in use in the workplace (Di Fiore & Souza, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, they can be used to measure others’ perceptions as well as provide insight into real behaviors (Martel et al, 2017). Indeed, peer team member ratings are positively related to experience level (Nuñez-Thompson et al, Accepted) and objective performance outcomes in real-world teams (Anwar et al, 2019; Ohland et al, 2012). Peer ratings are widely used in academic settings and are projected to increase in use in the workplace (Di Fiore & Souza, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Students still experience some level of distraction at any level of learning. This behavior was especially true in the classes related to technology and computer science 9 . Because of these results, in this study, we focus on behaviors that students could show when engaged in active learning activities.…”
Section: Introductionmentioning
confidence: 84%
“…For example, some studies reported that interactive activities resulted in more engaged students' behaviors; others have reported declining student engagement and lower satisfaction with using student-centered activities in classes 8 . Also, prior studies suggested that distraction does not completely dissipate as the learning activities move from passive to interactive 9 . Students still experience some level of distraction at any level of learning.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, many efforts have been reported emphasizing the importance of creating a learning environment that helps students develop their skills in programming courses [5,10]. Additionally, studies have reported the need of effective learning environments and pedagogical techniques to improve students' performance [11,12] Commonly used methods have been suggested to include environments with project-based learning, introduce pair programming, use language-independent courses, or provide practice opportunities in courses [13,14].…”
Section: Introductionmentioning
confidence: 99%